Vertex Labeled Energy of Edge-Removed Complete Graphs - Nursyahida, Salwa; Rana, Salsabiil; Sukaesih, Esih (KUBIK: Jurnal Publikasi Ilmiah Matematika, 2023)
Suppose Î“ is vertex labeled graph by its degree. The (i,j)-th entry of vertex labeled matrix of Î“ is label sum of different vertices v_i Â and v_j Â if there are paths between them, and 0 otherwise. Vertex labeled energy of Î“ is absolute sum of its vertex labeled matrix eigenvalues. In this paper, we provide value of vertex labeled energy of edge-removed complete graph.